2022
DOI: 10.3390/s22249702
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Void Defects behind Tunnel Lining through GPR forward Simulation

Abstract: Voids, a common defect in tunnel construction, lead to the deterioration of the lining structure and reduce the safety of tunnels. In this study, ground-penetrating radar (GPR) was used in tunnel lining void detection. Based on the finite difference time domain (FDTD) method, a forward model was established to simulate the process of tunnel lining void detection. The area of the forward image and the actual void area was analyzed based on the binarization method. Both the plain concrete and reinforced concrete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Wu suggested a method for detecting voids using GPR and a forward model based on the FDTD method. It was observed that the response pattern of the voids depends on their width, and waterfilling expands the response range and produces virtual images (Wu et al, 2022). Despite the interference from rein-forcement bars, the central location of the voids can still be precisely located using 3-D GPR.…”
Section: Introductionmentioning
confidence: 99%
“…Wu suggested a method for detecting voids using GPR and a forward model based on the FDTD method. It was observed that the response pattern of the voids depends on their width, and waterfilling expands the response range and produces virtual images (Wu et al, 2022). Despite the interference from rein-forcement bars, the central location of the voids can still be precisely located using 3-D GPR.…”
Section: Introductionmentioning
confidence: 99%
“…With the primary objective of resolving the data signal-to-noise ratio and multi-path interference problems to offer assurances for data feature extraction, Lei et al [ 10 ] suggested an air-coupled geo-radar detection technique provided by F-K filtering and BP migration. A strong technical guarantee for single defect detection was provided by the GPR forward simulation model developed by Wu et al [ 11 ], but since tunnel defects are frequently made up of hollow, water-filling, and non-compactness, the model’s generalization ability is not ideal. Ali et al [ 12 ], using Faster-RCNN and YOLOv3 networks as well as conventional detection techniques, examined the performance of concrete structures; the findings revealed that the convolutional neural network-based detection strategy had greater detection accuracy and localization precision.…”
Section: Introductionmentioning
confidence: 99%
“…During the process of tunnel construction, the lining may develop a variety of defects or diseases due to various reasons [ 2 , 3 , 4 , 5 , 6 ]. One of the more common problems is voids on the vault [ 7 ].…”
Section: Introductionmentioning
confidence: 99%